The origin of Alpine breed: An atavistic phenomenon - KARATZAS (Γ. ΚΑΡΑΤΖΑΣ), G.; MALLINIS (Δ. ΜΑΛΛΙΝΗΣ), D.; TSERTSENES (Ν. ΤΣΕΡΤΣΕΝΕΣ), N. (Journal of the Hellenic Veterinary Medical Society, 2018)
The objective of this study was to describe the origin of the Alpin breed through an atavistic phenomenon. A purebreed Alpin buck appeared horns entirely different from those of its breed. A number of different parameters were studied, such as the number of chromosomes, the body conformation, the colour, the horns, the head as well as the body dimension data. These parameters were compared with those from ten Alpin breed bucks and from thirteen aegagrus of the same age. We found that the horns of the buck that we examined were similar with those of the aegagrus. This seems to be an atavistic phenomenon. It is possible the Alpinbreed to have as ancestor the aegagrus. The clockwise of the left horn, which appears in the Alpin bucks, is a characteristic of the Capra prisca. This event points to the possibility that the Alpin breed is the product of a crossing of domestic goats, which originated from Capra prisca and Capra aegagrus.